Altered Cortical Cholinergic Network in Parkinson’s Disease at Different Stage: A Resting-State fMRI Study - Sheng, Wenshuang; Guo, Tao; Zhou, Cheng; Wu, Jingjing; Gao, Ting; Pu, Jiali; Zhang, Baorong; Zhang, Minming; Yang, Yunjun; Guan, Xiaojun; Xu, Xiaojun (Frontiers in Aging Neuroscience, 2021)
The cholinergic system is critical in Parkinson’s disease (PD) pathology, which accounts for various clinical symptoms in PD patients. The substantia innominata (SI) provides the main source of cortical cholinergic innervation. Previous studies revealed cholinergic-related dysfunction in PD pathology at early stage. Since PD is a progressive disorder, alterations of cholinergic system function along with the PD progression have yet to be elucidated. Seventy-nine PD patients, including thirty-five early-stage PD patients (PD-E) and forty-four middle-to-late stage PD patients (PD-M), and sixty-four healthy controls (HC) underwent brain magnetic resonance imaging and clinical assessments. We employed seed-based resting-state functional connectivity analysis to explore the cholinergic-related functional alterations. Correlation analysis was used to investigate the relationship between altered functional connectivity and the severity of motor symptoms in PD patients. Results showed that both PD-E and PD-M groups exhibited decreased functional connectivity between left SI and left frontal inferior opercularis areas and increased functional connectivity between left SI and left cingulum middle area as well as right primary motor and sensory areas when comparing with HC. At advanced stages of PD, functional connectivity in the right primary motor and sensory areas was further increased. These altered functional connectivity were also significantly correlated with the Unified Parkinson’s Disease Rating Scale motor scores. In conclusion, this study illustrated that altered cholinergic function plays an important role in the motor disruptions in PD patients both in early stage as well as during the progression of the disease.